(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted mainly to have an understanding about the farmers perception of environmental degradation due to use of pesticides. Data for the study were collected by personal interviewing from 69 randomly selected farmers of Kabaria kanda village of sadar upazila of Mymensingh district during the period of 01 November to 15 November, 2012. Pearsons product moment correlation co-efficient were computed to examine the relationship between the concerned variables. Perception on environmental degradation was reflected more in the young (30.4 percent) to middle age (42 percent) group compared to old age group. Majority (72.5 percent) of the farmers in the study area were found to have no organizational participation. The highest proportion (73.9 percent) of the respondents fell in the moderate knowledge category while none fell in less knowledge and 26.1 percent in the high knowledge category respectively. Only 1.4 percent of the farmers had moderately perception on environmental knowledge as compared to 98.6 percent favorable perception. Out of eight independent variables, five of them, i.e. years of schooling, farm size, annual family income, media exposure and knowledge on the use of agro-chemicals had positive relationships with their perception of environmental degradation due use of pesticides. Only three independent variable i.e. age, household size and organizational participation had no relationship with their perception of environmental degradation due use of pesticides. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22079 J. Environ. Sci. & Natural Resources, 6(2): 13-18 2013